"Classroom Techniques To Develop Students' EnglishWriting Skill: A Naturalistic Study At SmpMuhammadiyah 1 Surakarta" - Pratiwi, Mia Dian, Prof. Dr. Endang Fauziati, M. Hum (2016)
Mia Dian Pratiwi. A320120116. CLASSROOM TECHNIQUES TO DEVELOP STUDENTS' ENGLISH WRITING SKILL: A NATURALISTICS STUDY AT SMP MUHAMMADIYAH 1 SURAKARTA. Research Paper. School of Teacher Training and Education. Muhammadiyah University of Surakarta. 2016. This study is aimed to describe (1) classroom techniques used by the teacher to develop students' English writing skill (2) the purposes of each classroom technique (3) the teacher's roles (4) the student's roles. This type of the research is descriptive qualitative research, especially naturalistic study. The method of collecting data is observation and interview. The result is some classroom techniques used by the teacher to develop students' English skill, especially writing skill such as: writing based on picture, writing based on template, writing a card, dictation, writing based on topic, join writing in a group, fillin the blank sentence, writing based on random sentence. The teacher has roles as controller, teacher as organizer, teacher as prompter, teacher as resource, teacher as tutor, teacher as observer, and teacher as model. The students has roles as planner, students as group, students as tutor, students as monitor and evaluator. The conclusion of this study is that the use of various classroom techniques in the teaching - learning process by English teachers in SMP Muhammadiyah 1 Surakarta can develop the students' English skill especially writing skill. By using various classroom techniques can make students interested and enjoyed in teaching-learning English language. Students become more active and creative in teaching writing skill. Based on the result, classroom techniques used by teacher are very important and they can make the students do not feel bored and lazy in the teaching - learning process of English writing skill. Key words: Classroom techniques, writing skill, teacher's roles, student's roles.